A rare case of paediatric astroblastoma with concomitant MN1‐GTSE1 and EWSR1‐PATZ1 gene fusions altering management. (22nd February 2021) - Chadda, Karan R.; Holland, Katherine; Scoffings, Daniel; Dean, Andrew; Pickles, Jessica C.; Behjati, Sam; Jacques, Thomas S.; Trotman, Jamie; Tarpey, Patrick; Allinson, Kieren; Murray, Matthew J.; ,
Abstract : In a case of astroblastoma, methylation analysis was uninformative, with no clustering with known CNS‐HGNET‐MN1 cases. Whole genome sequencing however identified a novel MN1‐GTSE1 gene fusion (image), confirming the diagnosis of astroblastoma, as well as an EWSR1‐PATZ1 gene fusion. Whole genome sequencing, alongside methylation profiling and conventional neuropathology, will continue to lead to improved diagnostics and prognostication for children with brain tumours.